PENGARUH KETERAMPILAN METAKOGNISI TERHADAP PENGUASAAN KONSEP DAN BERPIKIR KRITIS MELALUI TPS - Vera Darmiyanti; Undang Rosidin; Viyanti - (Jurnal Pembelajaran Fisika, 2013)
The objectives of this research are to know: the positive influences the significances of metacognition toward the competence of the concepts of physics for senior high school by cooperative model with think pair share; are there positive influences and significances of metacognition skills toward critical thinking for senior high school students, by cooperative model with think pair share type. This research uses one-shot case study design. Those influences can be measured by holding final test or post test for the students after the learning process and metacognition skills, by cooperative learning model with think pair share type. The competence of physics concepts and critical thinking of metacognition skills of students were examined by regression test. Based on this research, can be concluded that: there are positive influences and significances of metacognition skills toward the competence of physics concepts through cooperative learning model with think pair share type; there are positive influences significances toward critical thinking of senior high school students by cooperative learning model with think pair share type. Keywords : metacognition skills, the competence of concepts, criticsl thinking, cooperative learning model with think pair share type.